"Discussion on curing mechanism of triazine curing system - LIU Hai-hong, QUE Yong-chan, XUE Bing-feng, CUI Zhe, LIU Min-ying, FU Peng (Hecheng xiangjiao gongye, 2022)
Under the condition of changing amount of 2-dibutylamino-4,6-dimercapto-s-triazine （curing agent DB） and magnesium oxide alternately, the curing characteristics and physical and mechanical properties of chlorinated butyl rubber cured with them were investigated, and the curing mechanism was discussed by Fourier transform infrared spectroscopy and thermogravimetric analysis. The results showed that the combination of curing agent DB and magnesium oxide could cure chlorinated butyl rubber well and achieve “zinc free cure”. When the amount of magnesium oxide was fixed, the amount of curing agent DB of 1.0-1.5 phr （mass） was appropriate. Magnesium oxide could improve scorch and prolong curing time in the curing system. The crosslinking reaction was characterized by participation of allyl bonded chlorine atoms, the thiol group of triazine mercaptan reacted with ally chloride and disengaged hydrogen chloride to form a C—S crosslinking network, and magnesium oxide participated in the curing reaction as an acid receptor.